Three free sins : God's not mad at you - Brown, Steve, 1940- (New York : Howard Books, 2012)
"After years of trying to teach people to be holy, Dr. Brown became fed up with reaching for the impossible. And so one day on his nationwide radio program, he offered the outlandish promise of three free sins. Sounds too goo to be true? The truth, Brown says, is that it is true. Of course, Steve Brown can't really offer free sins, but what he vividly conveys is that while we can never lead a blameless life, we can relax in knowing that we are completely forgiven -- not just of three sins, but of all."
The impossible task of flying frogs -- How's it working for you so far? -- Repent! The end is near! -- Why can't we all just get along? -- Ain't gonna study war no more! -- The wuss factor -- When getting better doesn't matter -- The devil made me do it! -- A party down at the church -- Just don't let them! -- Are you crazy?
"The reason we're so bad is that we're trying so hard to be good"--Cover.
Includes bibliographical references.
Keywords: Grace (Theology); Sin -- Christianity